A Hybrid and Secure Priority-Guaranteed MAC Protocol for Wireless Body Area Network. (23rd February 2014) - Ullah, Sana; Imran, Muhammad; Alnuem, Mohammed
This paper introduces a hybrid and secure MAC protocol (PMAC) for WBAN. The PMAC protocol uses two contention access periods (CAPs) for accommodating normal and life-critical traffic and one contention-free period (CFP) for accommodating large amount of data packets. The priority-guaranteed CSMA/CA procedure is used in the CAP period, where different priorities are assigned to WBAN nodes by adjusting the backoff window size. In addition, a set of security keys is used to prevent illegal access to the network. Analytical expressions are derived to analyze the average delay, power consumption, throughput, and packet loss probability of the PMAC protocol. Results derived from these expressions are validated by computer simulations.